Unit Preparation Strategy for Mobile Border Security Operations in Papua (A Case Study of Battalion 613/RJA in 2021) - Mahfudz; Thomas; Tasdik (Journal of Education Religion Humanities and Multidiciplinary, 2026)
This research is motivated by the importance of unit readiness in supporting mobile border security operations in Papua, a region characterized by complex geographical conditions, limited infrastructure, and continuously evolving security threats. These conditions require unit preparation that is not only administrative in nature but also adaptive to actual operational conditions in the field. The existing problems indicate that the preparation of personnel, operations, and logistics has not yet been fully optimized to meet operational demands, particularly in terms of human resource quality, operational planning, and sustainable logistical support. The urgency of this study lies in the need to formulate a more effective, adaptive, and integrated unit preparation strategy to improve the success of mobile border security operations. The objectives of this research are to analyze the factors influencing unit preparation and to formulate an appropriate strategy for preparing military units to support mobile border security operations in Papua. This study employs a qualitative method with a case study approach. Data were collected through interviews, document analysis, and field observations to obtain comprehensive information. The analysis was conducted using the Security Theory developed by Barry Buzan (1991), the Ends, Ways, Means Strategy Theory proposed by Arthur F. Lykke (1989), the Deterrence Theory of Thomas C. Schelling (1961), the Readiness Theory of Francisco J. Herrera (2020), and the Military Unit Readiness Theory of Aris Sarjito (2024). The findings reveal that personnel preparation has been conducted systematically but has not yet fully adapted to Papua's geographical and socio-cultural conditions. Operational preparation still faces gaps between planning and actual field conditions, while logistical preparation remains suboptimal, particularly regarding distribution systems and material readiness. The study concludes that the existing unit preparation strategy is generally appropriate but requires improvements in contextual, integrative, and adaptive aspects to better meet operational requirements. Therefore, this study recommends refining personnel selection policies, enhancing the quality of pre-deployment training, strengthening operational planning, and optimizing logistical support systems to improve the effectiveness and sustainability of mobile border security operations in Papua.